Intrapersonal, Interpersonal, and Cultural Factors Supporting Leadership Effectiveness of Women Entrepreneurs fr. - Mangunsong, Frieda (UI Scholars Hub, 2009)
This is a research about effectiveness of businesswomen leadership in four different ethnic groups in Indonesia. The effectiveness is measured in a condition where the leadership is supported by several factors, such as intrapersonal skills, interpersonal skills and culture. The subjects of this research are 216 female leaders of business units that consist of at least 10 employees, from Bali in Bali, Java in central Java, Minangkabau in West Sumatra and Batak tribes (Karo, Angkola, Mandailing) in North Sumatra. The result of this research shows that the examination of hypotheses using the theoretical model consisting of intrapersonal factors (leadership intelligence, sex roles, educational background), interpersonal factors (assertiveness, leadership style and leadership behaviour), and culture (family, business environment, and cultural environment) can be used to explain leadership effectiveness, although the influence of the three factors above are not significant. Almost all business women have a transformational leadership style. A more meaningful parameter to measure female leadership effectiveness, a larger number of subjects in each ethnic group, and variations of business fields are suggested.